Rancang Bangun Aplikasi Point Of Sale (Pos) Pada Café Elite`S Coffee Berbasis Android - Cristian Sepriadi galla; Amelia Yusnita; Muhammad Nur Madani (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2026)
Elite’s Coffee Café still relies on manual transaction recording and sales data management processes, which often lead to recording errors, delays in report generation, and inefficient transaction data management. These issues reduce operational efficiency and make it difficult for the owner to monitor sales accurately.This study aims to design and develop an Android-based Point of Sale (POS) application to support sales transactions, product data management, and automatic sales report generation. The system was developed using the Waterfall method, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. The application was built on the Android platform with an integrated database to store and manage transaction data.The results show that the developed POS application simplifies transaction processing, accelerates sales recording, reduces data entry errors, and generates sales reports automatically in real time. Based on the testing results, all main features of the application function according to user requirements.In conclusion, the Android-based Point of Sale (POS) application for Elite’s Coffee Café successfully improves operational efficiency, speeds up customer service, and enables more accurate and organized sales data management.